BLENDED LEARNING DARI PERSPEKTIF PARA GURU SEKOLAH DI PONDOK PESANTREN - Muklason, Ahmad; Mahananto, Faizal; Anggraeni, Wiwik; Djunaidy, Arif; Riksakomara, Edwin (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2019)
To survive the industrial revolution 4.0 which was marked by the massive use of digital technology, educational organizations are expected to do digital transformation. However, unfortunately it is commonly known that there is a gap in the use of technology in Indonesia between big cities and regions, between modern education system and traditional education system. To reduce this gap, blended learning technology training was held aimed for teachers in the Darul Ulum Islamic boarding school in Peterongan, Jombang. Pondok Pesantren Darul Ulum Islamic is a boarding school with almost 10,000 students. In the Darul Ulum Islamic boarding school its self there are various educational units ranging from primary school to higher education. This study focuses on investigating the online learning technology adoption by teachers in Islamic boarding school, especially their perspective on the technology. Our findngs showed that they are very ready to adopt the technology.